Sensitive Colorimetric Hg2+ Detection via Amalgamation-Mediated Shape Transition of Gold Nanostars - Xu, Dong; Yu, Shufang; Yin, Yueqin; Wang, Suyan; Lin, Qinlu; Yuan, Zhiqin (Frontiers in Chemistry, 2018)
Reliable and sensitive methods to monitor mercury levels in real samples are highly important for environment protection and human health. Herein, a label-free colorimetric sensor for Hg2+ quantitation using gold nanostar (GNS) has been demonstrated, based on the formation of Au-Hg amalgamate that leads to shape-evolution of the GNS and changes in its absorbance. Addition of ascorbic acid (AA) to GNS solution is important for quantitation of Hg2+, mainly because it can reduce Hg2+ to Hg to enhance amalgamation on the GNSs and stabilize GNSs. In addition to transmission electron microscopy images, the distribution of circular ratios of GNSs in the presence of 2 mM AA and various concentrations of Hg2+ are used to show the morphology changes of the GNSs. Upon increasing the concentration of Hg2+, the average circular ratio of GNSs decreases, proving GNS is approaching to sphere. The morphology change alters the longitudinal localized surface plasmonic resonance (LSPR) absorbance of the GNSs significantly. Under the optimum conditions, our sensor exhibits a dynamic response for Hg2+ in the range of 1-4000 nM with a detection limit of 0.24 nM. Upon Increasing Hg2+ concentration, the solution color changes from greenish-blue, purple to red, which can be distinguished by the naked eye when the Hg2+ concentration is higher than 250 nM. Owing to having a high surface-to-volume ratio and affinity toward Hg0, the GNS is sensitive and selective (at least 50-fold over tested metal ions like Pb2+) toward Hg2+ in the presence of AA. Practicality of this assay has been validated by the analysis of water samples without conducting tedious sample pretreatment.